Konsep Manusia Menurut Dayak Wehea: Tinjauan Filosofis Berdasarkan Filsafat Ersnt Cassirer - Andinata, Yovinus (Universitas Katolik Parahyangan, 2024)
The focus of this research is to delve into the concept of humanity according to the Dayak Wehea, examined through Ernst Cassirer's philosophy. The Dayak Wehea upholds a distinctive tradition of customs that remains practiced by a significant portion of their community. These customary traditions include rituals surrounding birth, marriage, and death, which inherently contain a wealth of anthropological and philosophical values specific to the Dayak Wehea. Presently, these traditions face cultural degradation due to the overwhelming influence of modern culture. Consequently, this study is motivated by concern and awareness regarding the existence of the Dayak Wehea people, particularly the erosion of their noble traditions over time. The objective is to explore and document the traditional values of Dayak Wehea customs, specifically focusing on the human concept embedded within the three rituals: birth, marriage, and death. This exploration of anthropological values is guided by Ernst Cassirer's philosophical framework. Additionally, the research aims to provide readers with an understanding of the anthropological significance of these rituals. The methodology employed is qualitative, involving a literature review and data analysis. To ensure authenticity, interviews were conducted with key informants, notably traditional leaders who possess firsthand knowledge and continue to practice these customs. The findings reveal the Dayak Wehea's concept of humanity as symbolic beings, beings of noble dignity, relational beings, pilgrims of hope, and religious beings.